Key issues of health and safety for workers in residential aged care: An expert study - Seaward, Liz; Morgan, Damian; Thomson, Alana (Frontiers in Public Health, 2023)
Introduction: Residential aged care (RAC) represents a fast-growing sector within Australia’s health care system and is characterized by high levels of workplace injury. To better understand this injury problem, this study investigated key informant perspectives concerning sector occupational health and safety (OHS) focused toward key issues associated with the risk of worker injury. Method: Semi-structured interviews were undertaken with nine key informants representing (OHS) specialists, healthcare employers, regulators, worker association representatives and academic researchers in OHS or healthcare. Interviews were transcribed verbatim and analyzed using thematic analysis. Results: This study identified six themes on OHS within RAC including: i) the physical and emotional nature of the work, ii) casualization of employment, iii) prioritization, iv) workforce profile, v) OHS role construction, and vi) clinical standards. The study highlighted differences in OHS roles between RAC and other safety-critical sectors regarding governance and management of OHS. The key informants identified a propensity within RAC to downplay or disregard worker OHS issues justified through prioritizing resident safety. Further, neither OHS professional nor institutional logics are prominent in RAC leadership and decision-making where emphasis is placed on mandatory standards to maintain funding purposes. Several recommendations are made to address identified issues.